Structural and Electrochemical Studies of Copper(I) Complexes with Diethoxyphosphoryl‐1, 10‐phenanthrolines. Issue 21 (24th June 2014) - Mitrofanov, Alexander; Manowong, Machima; Rousselin, Yoann; Brandès, Stéphane; Guilard, Roger; Bessmertnykh‐Lemeune, Alla; Chen, Ping; Kadish, Karl M.; Goulioukina, Nataliya; Beletskaya, Irina
Abstract: Two series of copper(I) complexes with diethoxyphosphoryl‐substituted 1, 10‐phenanthroline ligands were synthesized and characterized in the solid state and in solution. The first comprised mixed‐ligand Cu I complexes with phenanthroline and triphenylphosphine. The second series includes bis‐chelates with two phenanthroline ligands. According to the X‐ray data for the six complexes, the ditopic phenanthroline ligands exhibit bidentate coordination to the copper(I) atom through two nitrogen atoms in both series. Solution equilibria involving different phenanthroline copper(I) species were studied by 1 H and 31 P NMR spectroscopy, electrochemistry, and spectroelectrochemistry. The solution speciation of these labile complexes is different for these two series and depends on the nature of solvent and the location of the phosphorus substituent on the phenanthroline backbone. Coordinating solvents can replace a bromide, triphenylphosphine, and even a phenanthroline ligand in the inner coordination sphere of the metal center. Copper(I) complexes with α‐substituted phenanthrolines easily dissociate even in noncoordinating solvents such as CH2 Cl2 and CHCl3 . Ligand‐exchange reactions leading to less sterically hindered species were observed under the utilized solution conditions. The coordination mode of the phenanthroline chelators does not change under any of the utilized solution conditions, and binding of the phosphoryl group to the metal center was never observed by spectroscopic or spectroelectrochemical methods. Abstract : Copper(I) complexes with diethoxyphosphoryl‐substituted 1, 10‐phenanthroline ligands are synthesized and characterized in the solid state and in solution by X‐ray diffraction, 1 H and 31 P NMR spectroscopy, electrochemistry, and spectroelectrochemistry.